Post a New Question


posted by on .

what is the F-^1



  • pre-calculus - ,

    Your notation is confusing and your equation is ambiguous without parentheses.

    If F(x) = 6/(x+4) = y,

    the inverse function F^-1 (x) is the operation that, if applied to y, will give you x.
    x +4 = 6/y
    x = (6/y) -4

    Finally, switch variables.

    F^-1(x) = (6/x) - 4

    Note that if you apply this inverse function to 6/(x+4), you get back x.

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question